Study on properties of bottom ash as cement partial substitution in cement composite - Mohd Redzuan Bin Talib (School of Environmental Engineering, University Malaysia Perlis, 2014)
The objective of this research were to identify properties of properties of cement composite with partial substitution of bottom ash as cement. Using bottom ash in the concrete, it can help to reduce the high environmental impact of concrete industries and to the rising demand of infrastructure.